Sosialisasi Generasi Muda Bijak dalam Menggunakan Media Sosial di Kelas X SMA Katolik 2 Kabanjahe - Ginting, Nurlia; Jenita Anjani Br Sembiring; Indah Simamora; Seri Nita Br Ginting Suka; Limarti Sipakkar; Perdana Perkalis Ginting (EDUPEDIA Publisher, 2024)
We must pay attention to understanding wisely and skillfully in using social media and if possible, this can also provide positive results for using social media. It is also hoped that when getting information via social media, the younger generation must really filter it first so that they can know the truth about the information. We also hope that the millennial generation must have ethics and be competent in using social media. According to Ardiansah and Maharani (2021) social media is a means or forum used to facilitate interaction between fellow users and has the nature of two-way communication, social media is also often used to build a person's self-image or profile, and can also be utilized by companies as media. marketing. Using social media as a marketing medium can be done by uploading photos to social media accounts such as Instagram and then they can be seen by consumers who follow the Instagram account. Do a more in-depth filter first, don't immediately accept the information at face value. The virtual world is very fast, in just a fraction of a second, the information has reached and been read by many people. 71 percent of internet use is among children and teenagers, for this reason supervision is needed from parents and the immediate environment. Parents are also expected to supervise their children and must also have knowledge about the bad effects of social media. Later, open discussions will also need to be held to build ethics in order to create healthy behavior for children in using the internet. Social media seems to have become an addiction for society, especially teenagers. Today's teenagers are synonymous with gadgets that they use almost 24 hours a day. Some of the social media most frequently used by teenagers are Facebook, Twitter, YouTube, Instagram, and Line. This is because social media has its own advantages and interests for its users and offers convenience that makes teenagers feel at home using it for a long time. Therefore, there must be education about appropriate use for students, limitations in using social media. The use of social media has become integral to our lives, especially children and teenagers. Therefore, there needs to be guidance for teenagers to be wiser in using social media because everything is on social media